2001
DOI: 10.2174/1381612013397483
|View full text |Cite
|
Sign up to set email alerts
|

Modifications in the upper or Velbenamine Part of the Vinca Alkaloids have Major Implications for Tubulin Interacting Activities

Abstract: Vinca alkaloids represent a chemical class of major interest in cancer chemotherapy. The lead compounds vinblastine and vincristine have been employed in clinical practice for more than thirty years and remain widely used to this day. Several hundred derivatives have been synthesised and evaluated for their pharmacological activities, the majority being modified in the vindoline moiety, bearing several reactive centers. These efforts led to the identification of the amido derivative vindesine, registered in Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Vincristine, vinblastine, and vindesine are the irst vinca alkaloids used as antitumor drugs. Vinorelbine is the irst new second-generation vinca alkaloid, while vinlunine, a bis-luorinated vinorelbine derivative, was synthesized by superacid chemistry and studied in phase I-III clinical trials [14,15].…”
Section: Microtubule-destabilizing Agentsmentioning
confidence: 99%
“…Vincristine, vinblastine, and vindesine are the irst vinca alkaloids used as antitumor drugs. Vinorelbine is the irst new second-generation vinca alkaloid, while vinlunine, a bis-luorinated vinorelbine derivative, was synthesized by superacid chemistry and studied in phase I-III clinical trials [14,15].…”
Section: Microtubule-destabilizing Agentsmentioning
confidence: 99%
“…Microtubule-targeting drugs (MTD), e.g., Vinca alkaloids and taxanes, are major cancer chemotherapeutic drugs largely used in many human tumoral diseases. Vinflunine, the newest Vinca alkaloid, currently in phase III clinical trials (2), is a fluorinated compound obtained by superacid chemistry (3). Similar to other MTDs, vinflunine suppresses microtubule dynamics both in vitro (4,5) and in living cancer cells (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Preclinical studies demonstrated that it has more activity than vinblastine or vinorelbine. 9,10 For example, in an orthotopic model of bladder cancer in mice, vinflunine was found to be more effective than vinorelbine.…”
mentioning
confidence: 99%